METHODOLOGICAL PRINCIPLES OF THE DEVELOPMENT OF ACME-ORIENTED MATURE PERSONALITY - Tkachenko, Oleksandr (PSYCHOLOGICAL JOURNAL, 2019)
The article presents the understanding of the acme-oriented mature personality (AOMP) as an integrative level-procedural formation, systemically structured along the vertical moral-ethical acme-vector and horizontal vector of the life path, which seeks to achieve its highest purpose as the realization of the "cause of life" (the specific characteristic of maturity). Case of life is defined as the necessary ability to do for the development of personality as support for the dynamic integrity of its subjectivity (as the first causality) and the corresponding integral ability of self and life implementation. The dialectical and general models of development of AOMP are presented, as well as a model of the system of acme-psychological principles. The principle of acme orientation (PAO) acts as a systemic target and defines the vertical vector of the development of AOMP, which reproduces the “spiritual verticals” of the general dialectical model. The principle of mediation (PM) acts as a system-evolutionary and reproduces the dynamic essence of the general dialectical model. Its integration with PAO enables the development of a horizontal vector of the methodology for the development of AOMP due to existence and transcendence. The principle subject-action methodological (PSAM) is considered as a system-functional, integration with PAO and PM makes it possible to develop both a general and individual methodology for the development of AOMP. The principle of acme-socialization (PAS) or the realization of the cause of life is regarded as system-integrative and is a system-forming factor. Thanks to him, the unity and functioning of all previous principles in the integrated system of development of AOMP is ensured. Prospects for further research are related to the study of the problem of acme-socialization as the development of AOMP and the further development of social relations on a humanistic basis. According to the results of our empirical exploration, the modern example of the implementation of acme-socialization is demonstrated by the direct participants in the "Donbas War" military operations, whose personalities have radically changed under the influence of moral and ethical dominant.